Study on the Establishment and Optimization of Sandcastle Infrastructure Model. Issue 1 (September 2020) - Han, Zhixuan; Gao, Yuqiu; Ren, Shuyu; Chen, Depin
Abstract: Sand castle was created by the tourists on the beach for fun, then how to set up a stable sand castle under the condition of waves and tidal waves to get the honor of "sandcastles builder" has been their main concern. In this paper, considering the formation principle of sandcastle and the effect of the uncertain factors and the effect on the stability of the sand castle, the sandcastle infrastructure model is established and the 3D geometric model of the sand pile is optimized step by step. We start with sand heap discretization, the impact process of waves and tides is regarded as the external force acting on the sand, and the stress analysis shows that there are three kinds of stress conditions: no external force, one external force and two external forces. Then from the point to surface, the stress energy of the whole layer of sand is analyzed according to the two aspects of energy transfer dissipation and internal force failure dissipation. The optimal bearing capacity plane is approximately pentagon by annealing algorithm. Finally, from the surface to the solid, taking the self-weight of the sand pile, the effective external force action and the seawater erosion action as the constraint conditions, the optimal tilt angle of the plane stack is calculated to be 36.87° by measuring the risk degree of the overlaying slope Angle. Therefore, the oblique pentagonal body with an inclination angle of 36.87° is relatively stable.